Students’ Donating Behaviors through the Online Charitable Crowdfunding: A S-O-R Approach - Putri, Shaquila Dania; Tista Putriana, Vima (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2024)
This study aims to determine behavior of donating by students at Universitas Andalas. The samples are selected using the convenience sampling method. The data obtained from 222 respondents will be analyzed using the PLS-SEM (SmartPLS). The main findings shows that female students tend to donate more than male students at Universitas Andalas, both in terms of frequency and the amount of donation. The second main finding is there seems to be no correlation between level of expenditures per month with amount of donation, and faculty where the student studies also relate to the donation amount and frequency. The practical implications of this study are for crowdfunding platform providers, website features and technology design need to be considered and managed properly considering that web quality has a significant effect on empathy and perceived credibility. Considering the potential of charitable crowdfunding between university students that is relatively high, studies related to the factors influencing charitable donations made through university students remain scarce.